“Worst experience in my life”: Conditions of Confinement in Incarcerated Settings During the COVID-19 Pandemic - Montagnet, Chase (Criminal justice review, 2024)
Much is unknown about the impact of the COVID-19 pandemic on the carceral experience. Firsthand accounts, however, can illuminate how the virus traveled through correctional institutions and how operational changes intended to mitigate virus transmission altered daily life for incarcerated people. Analyzing semi-structured interviews with 53 individuals released from state prisons, county jails, and halfway houses in a northeastern U.S. state between October 2020 and June 2021, this study explores the shifting conditions of confinement in the early months of the pandemic, as well as how incarcerated individuals experienced the pandemic in terms of their mental and physical health, safety, and trust in correctional institutions. Interviewees described the spread of COVID-19 in correctional environments and how it led to several pandemic-related changes, such as stoppages or adjustments to programs, visits, recreation time, and movement around the facility. The data ultimately suggest that pandemic lockdown measures, instituted to prevent virus transmission, led to environments akin to solitary confinement and compromised the ability of incarcerated individuals to connect with loved ones, exacerbated their fears about contracting the virus, and further eroded their trust in correctional institutions.